Psychosocial Risks, Work Engagement, and Job Satisfaction of Nurses During COVID-19 Pandemic - Giménez-Espert, María del Carmen; Prado-Gascó, Vicente; Soto-Rubio, Ana (Frontiers in Public Health, 2020)
Context: COVID-19 pandemic is a serious health emergency that has affected countries all over the world. Health emergencies are a critical psychosocial risk factor for nurses. In general, psychosocial risks constitute serious problems as they impact workers' health, productivity, and efficiency. Despite their importance, few studies analyze nurses' psychosocial risks during a health emergency caused by a pandemic or analyze their perception of the emergency and its relation to such risks. Objectives: To analyze the perception of COVID-19 by nurses, especially about measures, resources, and impact on their daily work. Also, to analyze these professionals' psychosocial risks and the relationship between perception of COVID-19 and these risks. Methods: A descriptive correlational study was performed in a convenience sample of 92 nurses from two public hospitals in the Valencian Community (Spain), (74 women, 79.1%), aged 24–63 (M = 43.37, SD = 11.58). Data were collected via an online self-completed questionnaire during the rise of the pandemic from March 29 to April 8, when the number of infections went from 78,797 to 146,690. Results: The measures and resources available about COVID-19 are relatively low, and the impact on their work is high. Similarly, the most prominent psychosocial risks appear to be emotional work and workload. In contrast, nurses' work engagement is medium, and their satisfaction is high. Finally, there seems to be a negative and significant relationship between the information available to nurses, the measures implemented, and resources with some of their psychosocial risks, and a positive one with job satisfaction and work engagement. There is also a positive and significant relationship only between the impact of COVID-19 and their work inequality, but not for other risks. Conclusions: The resources, measures, and information can be a protective factor facing nurses' psychosocial risks, especially during a pandemic. Studying the relationships between psychosocial risk and perception of a health emergency would be relevant and fundamental to protecting and caring for nurses, health professionals, and society.